Using "residual" FNA rinse and body fluid specimens for next‐generation sequencing: An institutional experience. Issue 5 (18th December 2015) - Wei, Shuanzeng; Lieberman, David; Morrissette, Jennifer J. D.; Baloch, Zubair W.; Roth, David B.; McGrath, Cindy
Abstract : BACKGROUND: Tissue specimens are typically considered optimal for molecular testing; however, in the current era of personalized medicine, cytopathology specimens are increasingly recognized as potential sources for molecular testing. This is often accomplished by using cell block specimens and/or fine‐needle aspiration (FNA) smear preparations. In this study, the authors investigated the feasibility, performance, and quality of "residual" FNA rinse and body effusion fluids used for next‐generation sequencing (NGS). METHODS: Sequence data were generated from 17 malignancies in 16 patients from 13 FNA (10 lymph nodes, 1 lung, and 2 bone lesions) and 4 effusion (3 pleural and 1 pericardial) specimens. Malignancies included carcinomas (lung, breast, ovarian, and unknown primary), melanoma, and myeloma. Paired NGS testing was performed in 7 patients who had surgical biopsy or cell block specimens available. Routinely processed residual FNA rinse material and body fluids were used for DNA extraction and NGS (targeted gene panel). RESULTS: NGS was successfully performed on all 17 specimens. A significant amount of DNA was obtained from the residual FNA rinse (176.3 ng/μL) compared with the paired cell block slides (10.6 ng/μL). Two of the 10 lung adenocarcinomas (20%) demonstrated epidermal growth factor receptor ( EGFR ) mutations, including 1 leucine‐to‐arginine substitution at codon 858 (L858R) in exon 21 and 1 codon 2235_2249 deletion (resulting in an in‐frame deletion of 5 amino acids from position 746 to 750 [glutamic acid, leucine, arginine, glutamic acid, and alanine]; E746_A750del) in exon 19. Three KRAS [Kirsten rat sarcoma viral oncogene homolog] mutations, 1 BRAF (v‐Raf murine sarcoma viral oncogene homolog B1) mutation, and 1 NRAS (neuroblastoma RAS viral oncogene homolog) mutation were identified in the remaining lung adenocarcinomas. Patients who underwent paired testing demonstrated 100% concordant mutations. CONCLUSIONS: Targeted NGS can be performed on residual FNA rinse and body fluid specimens. This approach is particularly important when a paucicellular cell block or biopsy specimen is encountered. Cancer Cytopathol 2016;124:324–29 . © 2015 American Cancer Society . Abstract : Targeted next‐generation sequencing can be performed on residual fine‐needle aspiration rinse and body fluid specimens. This approach is particularly important when a paucicellular cell block or biopsy specimen is encountered.